Analisis Faktor-Faktor Yang Mempengaruhi Literasi Keuangan Pada Mahasiswa Program Studi Manajemen Universitas Pgri Semarang - Sinta Widyastuti (Jurnal Ilmiah Manajemen Bisnis dan Ekonomi Kreatif, 2022)
This study aims to analyze the factors that affect financial literacy by using the variablesof class, Grade Point Average (GPA) and parents' income. Respondents from this studywere Management Students class 2017, 2018 and 2019 PGRI Semarang University witha total sample of 238 students. The data collection method in this study used aquestionnaire method distributed via google form with a total of 20 items. The samplingtechnique in this study used simple random sampling and the calculation of the number of samples used the Slovin formula. The data analysis method used is descriptiveanalysis and multiple regression with SPSS 22. The results of this study indicate that there is a negative and insignificant effect betweenthe variable force and financial literacy with an effect of 07.6%, there is a positive andsignificant influence between the Cumulative Achievement Index (GPA) variable andfinancial literacy with an effect of 1.01%, there is a significant and significant effectbetween the variables income of parents with financial literacy with an effect of 1.41%.Based on the results of the research that has been done, the value of Adjusted R Squareis 0.032 which can be concluded that the Force, GPA and Parents' Opinionsimultaneously affect financial literacy by 3.2%. While the remaining 96.8% is explainedby variables outside this research model.